A Dual‐Process Motivational Model of Social and Economic Policy Attitudes. Issue 1 (26th June 2013) - Perry, Ryan; Sibley, Chris G.
<x xml:space="preserve">Abstract</x> The dual process model (DPM) of ideology and prejudice suggests that right‐wing authoritarianism (RWA) and social dominance orientation (SDO) should differentially predict support for social versus economic policies. We test a differential prediction hypothesis in which support for social policies should be predicted by RWA, and support for economic policies should be predicted by SDO. We further test a dual mediation hypothesis suggesting that RWA and SDO differentially mediate the indirect effects of distinct combinations of personality traits and social worldviews on these policy attitudes. The hypothesized model provided a reasonable fit in a large New Zealand sample (N = 6, 886). Policy attitudes thus consist of at least two dimensions: social versus economic. Individual differences in these attitudes are differentially predicted by RWA and SDO—in much the same way as generalized intergroup attitudes and prejudice.